Women's experiences with deciding on neoadjuvant systemic therapy for operable breast cancer: A qualitative study - Anne Herrmann; Alix Hall; Nicholas Zdenkowski (Elsevier, 2018)
Objective: We explored, qualitatively, in a sample of Australian early-stage breast cancer patients eligible for neoadjuvant systemic therapy (NAST): (i) their understanding of the choice of having NAST; (ii) when and with whom the decision on NAST was made; and (iii) strategies used by patients to facilitate their decision on NAST. Methods: A sub-sample of patients participating in a larger intervention trial took part in this study. A total of 24 semi-structured phone interviews were analyzed using framework analysis. Results: A number of women perceived they were not offered a treatment choice. Most patients reported that the decision on NAST was made during or shortly after the initial consultation with their doctor. Women facilitated decision-making by reducing deciding factors and "claiming" the decision. Most women reported that they made the final decision, although they did not feel actively involved in the decision-making process. Conclusions: When deciding on NAST, patient-centered care is not always delivered to patients. Clinicians should emphasize to patients that they have a treatment choice, explain the preference-sensitive nature of deciding on NAST and highlight that patients should be involved in this treatment decision. Providing patients with appropriate time and tailored take-home information might facilitate patient decision-making. Process-orientated research is needed to adequately examine patient involvement in complex treatment decisions.